Automatic Safety Monitoring System of Railway Signal Light Based on Intelligent Learning Algorithm - Jianjun Wu (Forest Chemicals Review)
Railway transportation is an important part of China’s transportation sector. In recent years, with the rapid development of science and technology, the speed of trains has been increased many times, and the density of trains has continued to increase. How to ensure the safety of rail transit has become a concern of people. This paper studies the railway signal light automatic safety monitoring system based on the intelligent learning algorithm, understands the relevant knowledge of the railway signal light automatic safety detection based on the literature data, and then designs the railway signal light automatic safety monitoring system based on the intelligent learning algorithm, and the monitoring algorithm used in the system is tested, and the test results show that the algorithm in this paper has good sensitivity to anomaly detection, and samples with low anomalies have a higher resolution, and the amplitude of anomalies varies greatly, covering non-self-space smaller, it can describe in detail the variation of the abnormality of the sample from its own space.